Accelerating the Mdx Heart Histo-Pathology through Physical Exercise - Jacopo Morroni; Leonardo Schirone; Daniele Vecchio; Carmine Nicoletti; Luca D’Ambrosio; Valentina Valenti; Sebastiano Sciarretta; Biliana Lozanoska-Ochser; Marina Bouchè (Life, 2021)
Chronic cardiac muscle inflammation and fibrosis are key features of Duchenne Muscular Dystrophy (DMD). Around 90% of 18-year-old patients already show signs of DMD-related cardiomyopathy, and cardiac failure is rising as the main cause of death among DMD patients. The evaluation of novel therapies for the treatment of dystrophic heart problems depends on the availability of animal models that closely mirror the human pathology. The widely used DMD animal model, the mdx mouse, presents a milder cardiac pathology compared to humans, with a late onset, which precludes large-scale and reliable studies. In this study, we used an exercise protocol to accelerate and worsen the cardiac pathology in mdx mice. The mice were subjected to a 1 h-long running session on a treadmill, at moderate speed, twice a week for 8 weeks. We demonstrate that subjecting young mdx mice (4-week-old) to “endurance” exercise accelerates heart pathology progression, as shown by early fibrosis deposition, increases necrosis and inflammation, and reduces heart function compared to controls. We believe that our exercised mdx model represents an easily reproducible and useful tool to study the molecular and cellular networks involved in dystrophic heart alterations, as well as to evaluate novel therapeutic strategies aimed at ameliorating dystrophic heart pathology.